Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Anugrah Mitra Investa Depok - Annisa Febriyani; Rosento Rosento (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study is entitled "The Effect of Work Motivation and Job Satisfaction on Employee Performance at PT Anugrah Mitra Investa". Human resources are important elements needed by companies to achieve their goals. Work motivation and job satisfaction are two main factors that can affect employee performance. Lack of motivation and job satisfaction in working makes employee performance less than optimal in achieving the goals of an organization. This study aims to determine how much influence Work Motivation and Job Satisfaction have on employee performance partially and simultaneously. The sample of this study used a saturated sampling technique, with a total population of 45 employees. The data collection technique used was primary data, namely observation, interviews, and questionnaires. The data analysis method used is multiple linear regression using the SPSS version 26 application. The results of the partial hypothesis test (T-Test) on the Work Motivation variable (X1) show a calculated t value> t table, which is 2.715> 2.017 and has a sig of 0.10> 0.05, meaning that the Work Motivation variable (X1) has an effect and is significant to the Employee Performance variable (Y) at PT. Anugrah Mitra Investa Depok. And the results of the partial hypothesis test (T-Test) on the Job Satisfaction variable (X2) show that the calculated t value> t table is 3.121> 2.017 and a sig of 0.003 <0.05. , meaning that the Job Satisfaction variable (X2) has an effect and sig on Employee Performance (Y) at PT. Anugrah Mitra Investa Depok. The results of the simultaneous hypothesis test (F Test) on the Work Motivation variable (X1) and the Job Satisfaction variable (X2) show a calculated f value > f table, which is 21,500 > 4,047 and has a sig value of 0.001 < 0.005. So it can be concluded that the Work Motivation variable (X1) and the Job Satisfaction variable (X2) together (Simultaneously) have a significant effect on the Employee Performance variable (Y) at PT Anugrah Mitra Investa Depok.